Analisa Literasi Finansial, Sikap Finansial, dan Perilaku Finansial pada Milenial dan Generasi Z - Kristianti, Ika Puspita; Kristiana, Deranika Ratna (Universitas Muhammadiyah Gresik, 2023)
This research aims to analyze financial literacy and financial behavior in Indonesia, which specifically aims to find a correlation between the level of financial literacy and financial attitudes towards financial behavior. This research also analyzes and compares the influence of demographic characteristics on financial literacy levels. This research develops financial behavior theory in explaining and predicting the influence of financial literacy and financial attitudes on individual behavior. According to OECD & Lusardi (2019), financial literacy is divided into 3 dimensions, namely financial knowledge, financial attitudes and financial behavior. This research falls into the area of finance, which emphasizes the importance of financial education for individuals. This research uses a survey method containing a questionnaire to collect respondents' responses to indicators of financial literacy, financial attitudes and financial behavior. The results of data collection and processing show that financial literacy and financial attitudes are significantly correlated with individual financial behavior, namely that the level of financial literacy in men is higher than in women, and there is a higher financial attitude in individuals who have an educational background in economics. Considering that data collection uses an online survey, researchers cannot monitor respondents when filling out the questionnaire to ensure respondents' accuracy in filling out the survey. This research can be developed on various other indicators, such as education level, parenting style, and demographic location. In addition, a larger sample size will increase the reliability of the results.